The Effect Of Professionalism On The Prevention Of Fraud In Cooperatives With Anti-Fraud Awareness As A Moderation Variable - Mitan, Wilhelmina; Herdi, Henrikus; Sanga, Konstantinus Pati (SEAN Institute, 2024)
This study aims to test the influence of professionalism on fraud prevention with anti-fraud awareness as a moderation variable. This type of research is Causal-Comparative Research. The population in the study is Cooperative employees in the Sikka Regency Region with the level of position as Internal Auditor totaling 89 people, while the sampling technique in this study uses Saturated Sampling, which is the determination of samples if all members of the population are used as research samples. So that the sample in this study amounted to 89 respondents of Cooperative Internal Auditors in the Sikka Regency Area. The data collection techniques in this study are observation and questionnaire while the data analysis technique used is Moderated Regression Analysis. The results of the study show that (1) Professionalism has a positive effect on the prevention of fraud. (2) Anti-fraud awareness negatively moderates the influence of professionalism on the prevention of fraud. This means that Anti-Fraud Awareness weakens the influence of Professionalism on Fraud Prevention.